REAKTUALISASI DAKWAH WALI SONGO: GERAK DAKWAH KH SAID AQIL SIROJ DALAM MENEBAR ISLAM RAḤMATAL LIL ĀLAMIN - Lufaefi Lufaefi (IAIN Manado, 2018)
Abstract. Dakwah in the modern era, not a bit actualized by the ways of force, even up to spread hatred and rudeness. The hoax issues were made into a spear to 'legalize' the da'wah which he regarded as a very noble teaching. Because the meaning of such da'wah, as a result Islam is often blamed as a religion of terrorism. In the other, there is also a group of people who are afraid of Islam (Islamophobia). This is where the need to reconstruct da'wah models that seem radical. KH. Said Aqil Siroj, a national religious figure who now occupies the chair position of the Chairman of PBNU, has a distinctive model and movement of da'wah as actualized by Wali Songo when spreading Islam. The re-actualization of Wali Songo's teachings is echoed by KH. Said Aqil Siroj through persuasive approach, not force, keep the traditions, persistence of da'wah and reconstruct the meaning of Ahlussunah Wal Jama'ah as social values. Such a form of dakwah proved to have a devastating effect on the growth of Islamic values rahmatal lil 'alamin.Keywords: Wali Songo, KH. Said Aqil Siroj, Peace Da'wah, Islam Rahmatal Lil 'AlaminAbstrak. Dakwah di era modern sekarang, tidak sedikit diaktualisasikan dengan cara-cara memaksa, bahkan sampai dengan menebar kebencian dan kekasaran. Isu-isu hoax dijadikan tombak untuk ‘melegalkan’ dakwah yang dianggapnya sebagai ajaran yang sangat mulia. Karena pemaknaan dakwah yang demikian, akibatnya Islam sering dituding sebagai agama terorisme. Selain itu, muncul juga sekelompok orang yang takut akan Islam (Islamophobia). Di sinilah perlunya merekontruksi model-model dakwah yang terkesan radikal. KH. Said Aqil Siroj, tokoh agama Nasional yang kini menduduki kursi jabatan Ketua Umum PBNU, memiliki model dan gerak dakwah yang khas sebagaimana diaktualisasikan oleh Wali Songo ketika menyebarkan agama Islam. Reaktualisasi ajaran Wali Songo digemakan kembali oleh KH. Said Aqil Siroj melalui pendekatan persuasif, tidak memaksa, menjaga tradisi-budaya, kegigihan berdakwah dan merekonstruksi pemaknaan Ahlussunah Wal Jama’ah sebagai nilai-nilai sosial. Wujud dakwah demikian terbukti memberi efek dahsyat terhadap tumbuhnya nilai-nilai Islam rahmatal lil ‘alamin.Kata Kunci: Wali Songo, KH. Said Aqil Siroj, Dakwah Perdamaian, Islam Rahmatal Lil ‘Alamin.